2018
DOI: 10.1177/0266666918804861
|View full text |Cite
|
Sign up to set email alerts
|

Information behaviour of rural smallholder farmers in some selected developing countries: A literature review

Abstract: The literature from some selected developing countries has demonstrated that rural smallholder farmers need various information sources in pursuit of their goals of increasing production and improving their living standards. According to the sampled studies, the majority of smallholder farmers access information on crop production. Smallholder farmers are aware of information sources despite challenges faced in accessing and using information. The majority of smallholder farmers access information through pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…These results were fully consistent with that of Naveed (2012) and Naveed andAnwar (2013, 2015) as these studies also reported such barriers among rural farmers while obtaining needed information. These results were partially in line with those of Dutta (2009), Phiri, Chipeta and Chawinga (2019a, 2019b, and Zhang and Yu (2009), who reported information illiteracy, lack of visits of extension staff, lack of financial resources and lack of information centers as the primary hindrances to information access and use. However, these findings contradicted those of Ghafoor, Muhammad, and Chaudhary (2008) who reported that the citrus farmers face constraints while accessing information such as irrelevant TV/radio programs, no access to printed materials, non-cooperation and availability of extension field staff, illiteracy, citrus growers' lack of interest, lack of access to electronic media and poor technical knowledge of extension field staff.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…These results were fully consistent with that of Naveed (2012) and Naveed andAnwar (2013, 2015) as these studies also reported such barriers among rural farmers while obtaining needed information. These results were partially in line with those of Dutta (2009), Phiri, Chipeta and Chawinga (2019a, 2019b, and Zhang and Yu (2009), who reported information illiteracy, lack of visits of extension staff, lack of financial resources and lack of information centers as the primary hindrances to information access and use. However, these findings contradicted those of Ghafoor, Muhammad, and Chaudhary (2008) who reported that the citrus farmers face constraints while accessing information such as irrelevant TV/radio programs, no access to printed materials, non-cooperation and availability of extension field staff, illiteracy, citrus growers' lack of interest, lack of access to electronic media and poor technical knowledge of extension field staff.…”
Section: Discussionsupporting
confidence: 80%
“…Likewise, the studies of Dutta (2009), Ikoja-Odongo and Ocholla (2003) reported that information illiteracy, lack of visits of extension staff, and lack of financial resources as the primary hindrances to information access and use in Africa. Similar results were also reported in a review article by Phiri, Chipeta, and Chawinga (2019a). They reported that the major challenges faced by rural smallholder farmers of different developing countries while acquiring agricultural information included limited mobility, outdated information, ignorance, lack of extension agents, financial constraints, extension officers' limited knowledge and language barriers.…”
Section: Information Sourcessupporting
confidence: 82%
See 2 more Smart Citations
“…Idiake-Ochei, Onemolease and Erie (2016) espoused that the design of appropriate information services depends on understanding the information needs and challenges confronting users when they search for information. There is however, limited literature examining farmers' information seeking behaviour in developing countries (Phiri, Chipeta and Chawinga, 2018), with no documented study of the market information needs and information-seeking behaviour among smallholder livestock farmers within the study area. It is this research gap that the present study addressed.…”
Section: Introductionmentioning
confidence: 99%